Scaling Up Nutrition in Guinea-Bissau : What Will it Cost? - Kakietek, Jakub (World Bank, Washington, DC, 2017)
This paper builds on global experience and Guinea-Bissau's specific context to identify an effective nutrition approach along with costs and benefits of key nutrition interventions. It is intended to help guide the selection of the most cost-effective interventions as well as strategies for scaling these up. We estimate that the costs and benefits of implementing 10 nutrition-specific interventions in all regions of Guinea-Bissau would require a public investment of USD 17 million over five years (with about USD 3 million needed to maintain the current coverage of the interventions and USD 14 million needed to expand the coverage to reach 90 percent of the population). The two key conclusions of this paper are, first, that investing in nutrition in Guinea-Bissau is cost-effective based on international standards and, second, that investments in nutrition can generate very substantial health and economic benefits, with one dollar spent on nutrition interventions resulting in about 10 dollars of returns over the productive lives of children covered by high-impact nutrition interventions. Economic productivity could potentially increase by USD 120 million (discounted at 3 percent) over the productive lives of the beneficiaries, with an impressive internal rate of return of 9 percent annually. Theses findings point to a powerful set of nutrition-specific interventions that represent a high cost-effective approach to reducing child malnutrition and stunting in Guinea-Bissau.